Protection of personal Data: Between Traditional Texts and Technical Requirements - Boukhelfa, faycel (Journal of Legal Studies and Researches, 2023)
The objective of this study is to identify the legal guarantees of the personal data from any abuse or violation, especially with the advent of globalization and the accompanying of technological revolutions; wich allows the transmission of information at the global level, And what may result many risks such as assaulting privacy of individuals and their freedoms.